An Innovative Adaptive-Dimension Accordion Honeycomb for Circumferential Deformation - Hairui Zhang; Xianhang Li; Jiayuan Yang; Jingsong Yang (Applied Sciences)
This work presents a novel variable-dimension accordion honeycomb structure capable of achieving circumferential deformation, characterized by its uneven structural stiffness properties. Unlike current accordion honeycombs, our design employs a variable-dimension honeycomb configuration defined in the polar coordinate system, using independent shape and size parameters. We derive the circumferential stiffness of both the unit cell and the honeycomb through analytical and theoretical approaches based on the series–parallel mechanism (SPM), validated using finite element modeling (FEM). We evaluate the influence of unit cell angles and the number of units along orthogonal directions on circumferential stiffness, finding excellent agreement between theoretical and numerical models. Additionally, the results demonstrate that the novel honeycomb maintains a zero Poisson ratio during circumferential deformation, with the SPM remaining unaffected by geometric nonlinearity.